EASY AND FAST ESTIMATION OF THERMAL STABILITY OF HTS MAGNETS UNDER SIMPLE SITUATION (ETIMA, 2024)
Since the advent of 2nd-generation high-temperature superconducting (HTS) tapes which show great features on critical temperature, critical current density, and critical magnetic field, many researchers have been trying to generate ultra-high magnetic fields using HTS coils. One more promising technology is a no-insulation (NI) winding technique. This technique drastically suppresses the possibility of thermal runaway and burning-out of HTS coils. The interest into compact nuclear fusion magnets wound with HTS conductors is increasing rapidly within these 5 years. The simulation of such magnets larger than MRI/NMR HTS magnets takes an unfeasiblylong time. Therefore, we present a simple expression of the coil temperature rise under a simple assumption derived from the simple coil model to investigate the stability of large-scale magnets. The advantages of the method are simplicity, versatility, and nearly no computation, enabling a reduction of time in first-cut design.